A Corpus-Based Analysis of Interactive Markers in English Editorials of The News and Dawn News - Hafiz Muhammad Qasim; Feroza; Muhammad Shafqat Nawaz (Corporum)
The language of newspapers is characterized by the use of interactive markers. Such markers enhance the reading ability and make the text more reader-friendly. The study aimed to explicate two interactive markers used in Pakistani English newspaper editorials (PENE). It examined the use of frame markers and transitional markers in editorials of Pakistani English newspapers. The study followed the mixed-method technique as it was both qualitative and quantitative. The data for the analysis consisted of editorials of The News(TN) and Dawn News(DN). The corpus comprised 250 editorials from each newspaper published during 2017 and 2021. The data was inspected through AntConc 3.4.4.0 by following the interpersonal model of Hyland (2005). The frequencies of interactive markers in the editorial of TN and DN were identified, and the functions served by the use of interactive discourse markers were explained. The results indicated that DN contained more frame markers as well as transitional markers than TN. Frame markers were being used as a tool to shape and frame the discourse in the writing. The use of frame markers helped establishthe meaning contextually in the minds of the reader. The transitional markers were used to refer to the categories of contrasts and resemblances.